Self-Employment Among the Poor: Does It Pay Off? - Fisher, Monica; Lewin, Paul A.; Wornell, Emily J. (Journal of Poverty)
We find that in a typical year, between 2010 and 2019, there were an estimated 887,778 self-employed poor people in the U.S. The self-employed poor (vs. poor wage/salary workers) are less likely to belong to racial/ethnic minority groups, more educated, and more likely to be homeowners. Self-employment does not appear to pay off for America's poor. The poor experience an entrepreneurial earnings penalty (the loss in earnings being self-employed vs. working for wages) ranging between 12% and 43%. Future research is needed to understand why poor people choose self-employment, despite lower earnings on average than in wage work.